Preliminary Seismic Hazard Assessment of the Oral and Dental Hospital of Jenderal Soedirman University Indonesia. (2017) - Haryanto, Yanuar; Sudibyo, Gathot Heri; Effendi, Fransisca Cynthia Angelina
Abstract: The Oral and Dental Hospital of Jenderal Soedirman University was built in 2008. This building consists of 4 stories equipped with inpatient rooms, X-ray rooms, and laboratory. It is expected that with a main function as a public facility with a large number of people doing activities within it, the building has a high level of security when an earthquake occurred. This study aims to perform a preliminary seismic hazard assessment, i.e. an evaluation using a Rapid Visual Screening method and a Tier 1 Evaluation using FEMA 310. The results of the Rapid Visual Screening are a final level 1 score compared with a cut-off score of +2.00. If the final level 1 score is less than or equal to +2.00, the building requires the tier 1 evaluation. The Tier 1 Evaluation using FEMA 310 is performed to identify the potential deficiencies of the building. It consists of 3 sets of checklists that allow a rapid evaluation of the structural, nonstructural and foundation/geologic hazard elements of the building and site conditions. If the result of the tier 1 evaluation shows that the potential deficiencies of the building are identified, a more detailed evaluation of the building is recommended to perform. The results of the analysis show that from the Rapid Visual Screening method, the building has a final level 1 score of +0.3, while from the Tier 1 Evaluation there are Not-Compliant (NC) statements for structural and nonstructural components.